Growth of ferromanganese crusts on bioturbated soft substrate, Tropic Seamount, northeast Atlantic ocean - Luciana Ortiz Kfouri; Christian Millo; Amanda Estela de Lima; Carla Semiramis Silveira; Lucy Gomes Sant’Anna; Egidio Marino; Francisco J. González; Isaac Jamil Sayeg; James R. Hein; Luigi Jovane; Simone Bernardini; Paul A.J. Lusty; et al. (2021)
Peer reviewed